Neuro-control of seismically excited steel structure through sensitivity evaluation scheme. - Kim, Dong-Hyawn (Earthquake engineering & structural dynamics.)
The neuro-controller training algorithm based on cost function is applied to a multi-degree of freedom system; and a sensitivity evaluation algorithm replacing the emulator neural network is proposed. In conventional methods, the emulator neural network is used to evaluate the sensitivity of structural response to the control signal. To use the emulator, it should be trained to predict the dynamic response of the structure. Much of the time is usually spent on training of the emulator. In the proposed algorithm, however, it takes only one sampling time to obtain the sensitivity. Therefore, training time for the emulator is eliminated. As a result, only one neural network is used for the neuro control system. In the numerical example, the three storey building structure with linear and non-linear stiffness is controlled by the trained neural network. The actuator dynamics and control time delay are considered in the simulation. Numerical examples show that the proposed control algorithm is valid in structural control.